2016
DOI: 10.18488/journal.1/2016.6.3/1.3.177.191
|View full text |Cite
|
Sign up to set email alerts
|

Test-Taking Strategy Instruction in the National University Entrance Examination (NUEE) English Section

Abstract: This study attempted to investigate the effect of test-taking strategy training on Iranian students' performance on English section of the National University Entrance Examination (NUEE). To do so, 160 fourth grade high school students were randomly assigned to the control and experimental groups. The experimental group received 8 hours of test-taking strategy training along with samples of the NUEE exams, while control group only practiced the samples of the NUEE exams without being imposed to these strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…In addition, teachers' responses emphasized the negative effect of test anxiety on students' performance as was found by (Cassady & Johnson, 2002;Strnad, 2003). Furthermore, teachers' perceptions on the importance of test-taking strategies supports the findings of (Holmes, 2021;Igwe and Orluwene, 2019;Pour-Mohammadi & Abidin, 2018;Sweetnam, 2002;Takallou et al, 2016).…”
Section: Teachers" Responsessupporting
confidence: 62%
See 2 more Smart Citations
“…In addition, teachers' responses emphasized the negative effect of test anxiety on students' performance as was found by (Cassady & Johnson, 2002;Strnad, 2003). Furthermore, teachers' perceptions on the importance of test-taking strategies supports the findings of (Holmes, 2021;Igwe and Orluwene, 2019;Pour-Mohammadi & Abidin, 2018;Sweetnam, 2002;Takallou et al, 2016).…”
Section: Teachers" Responsessupporting
confidence: 62%
“…A meta-analytic literature review on test anxiety concluded that "test anxiety was significantly and negatively related to a wide range of educational performance outcomes, including [outcomes of] standardised tests, university entrance exams, and grade point average" (von der Embse et al, 2018, p. 483). Takallou et al (2016) found a relationship between students" grade point average (GPA) and the test-taking strategies they adopted. Several studies have found that lower second-language (L2) achievement is linked to higher levels of test anxiety and is associated with "deficits in listening comprehension, impaired vocabulary learning, reduced word production, low scores [in] standardised tests, low grades in language courses or a combination of these factors" (Gardner et al, 1997, p. 345).…”
Section: Relationship Of Test-taking Strategies To Test Anxiety and A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nemati 2016administered a re-test questionnaire on test-taking strategies to learners and then trained the same learners on test-taking strategies. Takallou et al (2016) also conducted an experimental study to train learners on test-taking strategies. As in our study, the learners were given a reading comprehension test paper consisting of ten multiple choice questions.…”
Section: Previous Studies and The Present Studymentioning
confidence: 99%
“…They yield different results. The data collection procedures used include think-aloud protocols (Nam, 2015), questionnaire (Nemati, 2016;Zhang, 2016), post-task interview (Lee, 2015), pre-test and post-test (Takallou et al, 2016), and think-aloud protocols as learners took the test and categorised the protocols into reading strategies (Nosrati, 2015).…”
Section: Previous Studies and The Present Studymentioning
confidence: 99%